Model of Legal Protection in E-commerce Transactions to Improve the Community Economy in Indonesia - Susanti Sari, Rini; Ferdiles, Luky; Muhammad Rusdi, Andi (Riviera Publishing, 2024)
Increasingly rapid technological advances, today's transactions can purchase goods easily from their own homes through e-commerce electronic commerce. The aim of this research is to provide protection to the community if they experience problems and to help consumers in cases where there is a loss in e-commerce transactions in order to support the government in improving the economy of the community in Indonesia. Based on Law no. 8 of 1999 concerning consumer protection which applies to e-commerce transactions carried out via the internet as a platform for upholding consumer protection, this research uses a normative juridical approach by examining literature and written law to connect consumer legal protection models with real world situations. Goods transactions occur online, public spaces that are vulnerable to legal problems prevent business actors from committing fraud in electronic transactions because of the many platforms available. Consumer protection laws will also protect consumers and prevent mistakes in doing business.